PENGARUH PENGGUNAAN VIDEO TUTORIAL APLIKASI E-SPT PADA MATA PELAJARAN PERPAJAKAN TERHADAP KETERLIBATAN PESERTA DIDIK - Tiara Inggrianti; Sri Sumaryati; Lies Nurhaini (Jurnal Pengembangan Pendidikan Akuntansi dan Keuangan (JPPAK), 2023)
Abstract This study aims to examine (1) the effect of using e-SPT application video tutorials on student engagement in behavioral aspects; (2) the effect of using e-SPT application video tutorials on emotional aspects of student engagement; (3) the effect of using e-SPT application video tutorials on student engagement in cognitive aspects; (4) the effect of using e-SPT application tutorial videos on student engagement. This research uses an experimental method with a quantitative approach. The population in this study was 108 learners. The sampling technique in this study used a cluster random sampling technique obtained a research sample of 72 students. Data collection techniques with questionnaires and documentation. The prerequisite tests of analysis in this study are normality test and homogeneity test. Hypothesis testing in this study is the Independent Sample t-Test test. The results of this study are (1) there is an effect of using e -SPT application video tutorials on student involvement in behavioral aspects with Sig. (2-tailed) 0.004 < 0.05; (2) there is an influence of the use of e-SPT application video tutorials on the involvement of emotional aspects of students with Sig. (2-tailed) values of 0.000 < 0.05; (3) there is an effect of using e-SPT application video tutorials on student engagement in cognitive aspects with Sig. (2-tailed) values of 0.000 < 0.05; (4) there is an effect of using e-SPT application video tutorials on student engagement with Sig. (2 -tailed) values of 0.000 < 0.05. Keywords: Video Tutorials, e-SPT Application, Student Engagement Abstrak Penelitian ini bertujuan untuk menguji (1) pengaruh penggunaan video tutorial aplikasi e-SPT terhadap keterlibatan peserta didik pada aspek perilaku; (2) pengaruh penggunaan video tutorial aplikasi eSPT terhadap keterlibatan peserta didik pada aspek emosional; (3) pengaruh penggunaan video tutorial aplikasi e-SPT terhadap keterlibatan peserta didik pada aspek kognitif; (4) pengaruh penggunaan video tutorial aplikasi e-SPT terhadap keterlibatan peserta didik. Penelitian ini menggunakan metode eksperimen dengan pendekatan kuantitatif. Populasi dalam penelitian ini sebanyak 108 peserta didik. Teknik pengambilan sampel dalam penelitian ini menggunakan teknik cluster random sampling diperoleh sampel penelitian sebanyak 72 peserta didik. Teknik pengumpulan data dengan kuesioner dan dokumentasi. Uji prasyarat analisis dalam penelitian ini adalah uji normalitas dan uji homogenitas. Pengujian hipotesis pada penelitian ini adalah uji Independent Sample t-Test. Hasil penelitian ini adalah (1) terdapat pengaruh penggunaan video tutorial aplikasi e-SPT terhadap keterlibatan peserta didik aspek perilaku dengan nilai Sig. (2-tailed) 0,004 < 0,05; (2) terdapat pengaruh penggunaan video tutorial aplikasi e-SPT terhadap keterlibatan peserta didik aspek emosional dengan nilai Sig. (2-tailed) 0,000 < 0,05; (3) terdapat pengaruh penggunaan video tutorial aplikasi e-SPT terhadap keterlibatan peserta didik aspek kognitif dengan nilai Sig. (2-tailed) 0,000 < 0,05; (4) terdapat pengaruh penggunaan video tutorial aplikasi e-SPT terhadap keterlibatan peserta didik dengan nilai Sig. (2-tailed) 0,000 < 0,05. Kata Kunci: Video Tutorial, Aplikasi E-SPT, Keterlibatan Peserta Didik